The complete guide to cardiac CT - Abramson, Simeon (New York McGraw-Hill, 2012)
"Based on the popular review courses of educator and radiologist Dr. Simeon Abramson, The Complete Guide to Cardiac CT is a timely, hands-on learning tool--one that will help you master every important aspect of cardiac CT, from acquisition to interpretation. This unique guide translates complex concepts and topics into understandable, relevant subject matter and includes contributions from international leaders in cardiac CT. Designed for the practical, day-to-day application of cardiac CT, the text also serves as a comprehensive visual resource more than 1000 laser-precise images and illustrations, all of which reflect the latest clinical acumen and cardiac imaging technology."--Publisher's website.
Section 1: Technology, technique, and dosimetry. The Evolution of CT Technology in Cardiac Imaging / Matthew J. Fleishman ; Technique / Simeon Abramson ; Dosimetry and Dose Reduction Techniques / Jonathon Leipsic and Brett Heilbron ; Artifacts, Pitfalls, and Remedies / Jason L. Kelly and Simeon Abramson. -- Section 2: The coronary arteries. Coronary Artery and Venous Anatomy / Simeon Abramson ; Myocardial Bridging / Abdel-Rauf Zeina ; Coronary Artery Anomalies / Simeon Abramson ; Aneurysm, Ectasia, and Dissection / Eric Kimura-Hayama and Simeon Abramson ; Plaque Detection and Characterization / Gabija Pundziute and Tineke P. Willems ; Coronary Artery Stenosis Assessment / Roger D. Bies and Carter Newton ; Coronary Artery Bypass Grafts / Eli Konen and Simeon Abramson ; Coronary Artery Stents / Eli Konen. -- Section 3: Beyond the coronary arteries. Cardiac CT Anatomy / Sebastian Leschka, Gudrun Feuchtner, and Simon Wildermuth ; The Myocardium / Simeon Abramson and Eli Konen ; The Pericardium / Lynn S. Broderick ; Cardiac Neoplasms and Pseudo-Tumors / Christopher J. Bennett, Phillip M. Young, and Philip A. Araoz ; Valvular Heart Disease / Ronan E. Ryan and Jonathan Dodd ; Myocardial Functional Analysis / Ronan E. Ryan and Jonathan Dodd ; Electrophysiology Applications / Farhood Saremi and Damian Sanchez-Quintana ; Congenital Heart Disease in the Pediatric Population / Hyun Woo Goo ; Congenital Heart Disease in the Adult Population / Nila J. Akhtar and Robert C. Gilkeson ; Myocardial Perfusion and Delayed Enhancement / Jonathan Lessick and Galit Aviram. -- Section 4: Controversy. Coronary CTA in the Acute Setting and the Triple Rule-Out Examination / Matthew J. Fleishman and Simeon Abramson ; Myocardial Perfusion PET / Samuel C. Wang ; Noncardiac CT Findings / Sopo Lin, Minh Lu, and Charles S. White ; Atherosclerosis Imaging in Primary Preventive Cardiology / Jeffrey L. Boone.
Includes bibliographical references.
Keywords: Heart -- Tomography; Heart -- Diseases -- Diagnosis; Heart Diseases -- diagnostic imaging; Radiography; Tomography, X-Ray Computed